International trade and economic insecurity - Mine Z. Senses (IZA World of Labor, 2017)
Whether or not international trade exposes workers to economic insecurity depends on the nature of the trade exposure of the firm, or industry, in which the worker is employed. Import-competing industries experience higher levels of risk to workers' incomes and employment, while firms that import intermediate production stages (“offshoring”) display bigger employment responses to small changes in workers' wages, and are more likely to shut down home factories. But offshoring also helps firms weather economic shocks. Offshoring firms are more likely to survive and provide greater employment stability to their workers.
Keywords: F6; F16; J3; 330; trade; volatility; income risk; displacement risk; firm survival; offshoring